Implementasi Program Madrasah Diniyyah dalam Mengembangkan Pendidikan Agama Islam di Madrasah Ibtidaiyyah - Suroningsih, Suroningsih; Sumarni, Sumarni; Aziz, Abdul; Luthfi, Ahmad; Maulana, Bagus Andrai; Munjayyanah, Munjayyanah; Munawwaroh, Nasywa Zunaibatul (Sekolah Tinggi Agama Islam Pati, 2023)
This study aims (1) to describe the implementation of the madrasah diniyah programme in developing Islamic religious education at MI Hidayatul Islam Gemong, and (2) to determine the contribution of the madrasah diniyah programme to the development of Islamic religious education materials at MI Hidayatul Islam Gembong. The method used in this research is a qualitative approach of case study research type. Data collection techniques used interviews, observation, and documentation. The main data source in this research is in the form of words and actions of informants, the rest is data from observation and documentation. Meanwhile, the data analysis technique uses data reduction techniques, data presentation, and conclusion drawing. The results of this study found that; (1) The implementation of the madrasah diniyah programme in developing Islamic religious education at MI Hidayatul Islam Gembong includes three stages, namely planning, implementation, and evaluation. The form of implementation is in the form of Islamic religious education learning activities in the classroom and also holding habituation activities. and also the implementation of the madrasah diniyah programme at MI Hidayatul Islam Gembong, all students are required to take part in the madrasah diniyah programme with the aim of developing students' knowledge of Islamic religious education material. The madrasah diniyah programme is carried out on Monday to Saturday, the time is after Formal learning activities. The activities are in the form of Islamic religious learning using several methods such as lectures, exercises/drills, stories, memorisation, and tours; (2) The contribution of the madrasah diniyah programme to the development of Islamic religious education materials at MI Hidayatul Islam Gembong is to increase students‘ knowledge in the field of Islamic religious education such as prayer material and tajweed, and improve students’ ability to write Arabic.